Marjin Pemasaran Ikan Patin (Pangasius sp.) di Pasar Jakabaring Kota Palembang - Lia Perwita Sari; Rih Laksmi Utpalasari (Seminar Nasional Lahan Suboptimal, 2019)
Sari LP, Utpalasari RL.  2019.  Marketing margin of patin fish (Pangasius sp.) in the Jakabaring market of Palembang City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 97-100. Palembang: Unsri Press. The potential of aquaculture in South Sumatra as a center for catfish production requires market information and market identification to find out where, how, when and to whom the product will be marketed. The purpose of this study was to determine the efficiency of marketing catfish in the city of Palembang based on marketing margins and the portion of prices received by producers (farmer's share). The research method uses the survey method. The research location was determined purposively, namely at the Jakabaring Market in Palembang. The withdrawal of research samples is done using the accidental sampling method. The taking of respondents through this method is collector traders, retailers I, retailers II and consumers of Patin fish buyers.The sample size of consumers in this study was set at 40 people, each of 10 respondents in each cluster. Data collected in the form of primary data and secondary data. Data were analyzed by descriptive qualitative and quantitative descriptive. The researcher used a qualitative method by analyzing the characteristics of each respondent and the pattern of marketing of catfish at the Jakabaring Market in Palembang. Quantitative analysis uses data obtained in the form of numbers, including marketing margins and farmer's shares. The results of the study state that the marketing margin and farmer's share, the most efficient pattern is the pattern of collecting traders - household consumers with a value of Rp 2,400 per kg and 87.64% respectively.Keywords: farmer’s share, market, sellers